Stress dependent ferroelectric properties of PZT and 0.9PZT - 0.1BLT ceramics - Navavan Thongmee (2018)
P-E hysteresis loops of PZT and 0.9PZT - 0.1BLT ceramics were determined using a modified Sawyer-Tower circuit. Ferroelectric properties investigation of the PZT and 0.9PZT - 0.1BLT ceramics under stress levels in the range of 0-175 MPa was also carried out. The result showed that with increasing stress level, a reduction of remanent polarization was clearly observed. The result was interpreted in terms of non-180° ferroelectric domain switching processes and the decrease in switchable part of domains induced by stress applied to these materials. Copyright © Taylor & Francis Group, LLC.